2015
DOI: 10.1039/c5ra00624d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and magnetic properties of graphite carbon encapsulated Fe3C nanoparticles for applications as adsorbents

Abstract: This paper reports the synthesis of graphite carbon encapsulated Fe3C nanoparticles (Fe3C/GC NPs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Raman spectroscopy is an effective method to characterize the bonding structure of carbon in CIPC‐T. The Raman spectra (Figure a) show only two peaks for CIPC‐550 (CIPC‐600): a highly intense G band at 1592.69 (1591.34) cm −1 and low‐intensity peak (D band) at 1351.23 (1342.88) cm −1 . Thus, mainly sp 2 amorphous carbon phases (i.e., sp 2 ‐hybridized disordered carbon units) exist in CIPC‐550 and CIPC‐600.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectroscopy is an effective method to characterize the bonding structure of carbon in CIPC‐T. The Raman spectra (Figure a) show only two peaks for CIPC‐550 (CIPC‐600): a highly intense G band at 1592.69 (1591.34) cm −1 and low‐intensity peak (D band) at 1351.23 (1342.88) cm −1 . Thus, mainly sp 2 amorphous carbon phases (i.e., sp 2 ‐hybridized disordered carbon units) exist in CIPC‐550 and CIPC‐600.…”
Section: Resultsmentioning
confidence: 99%
“…Iron carbide (cementite, Fe 3 C), as a typical transition metal carbide, has attracted extensive attention due to its excellent physicochemical properties, such as ceramic‐like mechanical behavior, high magnetic saturation, chemical stability, and catalytic activity, and has been widely exploited in the fields of batteries (lithium batteries and fuel cells), microwave adsorption, and generation of bioelectricity . Owing to the incorporation of carbon atoms into the metallic iron lattice, Fe 3 C has good electrical conductivity and interesting electronic structure compared with other iron compounds, such as iron metal, iron oxide, and iron nitride …”
Section: Introductionmentioning
confidence: 99%
“…In this method, the urea partially replaced the water in the first coordination sphere around the metal ion, forming long, polymeric, complex structures, presumably due to secondary coordination via the amide groups and hydrogen‐bridge formation between urea moieties. Subsequently, our group also reported the synthesis of Fe 3 C by using melamine, and proposed the corresponding mechanism, as shown in Figure . Besides small molecules like urea and melamine, polymers such as gelatin were also found to be able to prepare iron carbides.…”
Section: Synthesis Strategymentioning
confidence: 99%
“…Wang et al. reported Fe 3 C nanoparticles with porous carbon, which were homogeneously embedded in porous carbon sheets, and played significant roles for adsorbing organic pollutants and separating from aqueous solution . In this work, it could be observed that all the dyes were adsorbed completely due to high adsorption capacity of porous carbon sheets and the used adsorbents, possessing suitable saturation magnetization, could be separated easily from the aqueous suspension with an external magnet, which was of great importance for practical applications.…”
Section: Applicationsmentioning
confidence: 99%
“…20 This composite exhibited high adsorption capacity (150 mg/g) of rhodamine B. Core-shell graphite carbon encapsulated Fe 3 C nanoparticles have been synthesized by Wang et al with a saturation magnetization value of 61.5 emu/g. 21 They were used to adsorb methylene blue (MB), and showed an MB adsorption capacity of 33.1 mg/g. These magnetic composite materials exhibited good adsorptive property and magnetic recycling performance, but they cannot be continuously produced, and byproducts existed in the¯nal product.…”
Section: Introductionmentioning
confidence: 99%